2014
DOI: 10.1167/iovs.14-14143
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal and Retinal Thickening in Severe Preeclampsia

Abstract: PURPOSE.To compare choroidal thickness and retinal macular volume (RMV) among three groups of women: severe preeclampsia postpartum, normotensive postpartum, and normotensive nongravid. While visual disturbances often accompany severe preeclampsia, the underlying choroidal and retinal changes responsible for these symptoms have not been described.METHODS. This case-control study was based on 15 severe preeclampsia cases and 15 ethnicityand parity-matched normotensive controls recruited during the postpartum ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Four studies [21-23, 32] with a total of 194 participants (82 preeclamptic patients and 112 healthy nonpregnant women) were included. As shown in Figure 5, the CT of preeclampsia (μm, WMD = 54.30, 95% CI: –13.40 to 122.01) was not significantly different from the nonpregnancy group (Test of WMD = 0: z = 1.57, p = 0.116).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [21-23, 32] with a total of 194 participants (82 preeclamptic patients and 112 healthy nonpregnant women) were included. As shown in Figure 5, the CT of preeclampsia (μm, WMD = 54.30, 95% CI: –13.40 to 122.01) was not significantly different from the nonpregnancy group (Test of WMD = 0: z = 1.57, p = 0.116).…”
Section: Resultsmentioning
confidence: 99%
“…This leak sometimes accumulates behind the retina, and retinal detachment occurs. This general concept may still be valid: pre‐eclamptic patients had thicker choroidal and retinal layers . Some other studies suggested a more delicate pathophysiological mechanism: choroidal vessel abnormality may cause HDP‐related retinal detachment.…”
Section: Discussionmentioning
confidence: 96%
“…This general concept may still be valid: pre-eclamptic patients had thicker choroidal and retinal layers. 11 Some other studies suggested a more delicate pathophysiological mechanism: choroidal vessel abnormality may cause HDP-related retinal detachment. This may be particularly true of retinal detachment in patients with HELLP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…17 Therefore; retinal and choroidal markers could serve as novel predictive markers of severe preeclampsia. This further establishes the need of routine ophthalmoscopic examinations in all preeclamptic mothers irrespective of visual complaints.…”
Section: Discussionmentioning
confidence: 99%